Metformin in Oncology - How Far Is Its Repurposing as an Anticancer Drug? - Pácal, Lukáš; Kaňková, Kateřina (Klinicka onkologie, 2020)
BACKGROUND: Metformin is the most commonly used antidiabetic drug with a plethora of proven metabolic and cardiovascular beneficial effects and exceptional safety profile. On top of the established metabolic effects, retrospective epidemiologic evidence shows that metformin use is associated with decreased cancer risk and/or improved disease prognosis in diabetic cancer patients on metformin compared to those treated with different antidiabetic drugs. This is a sound argument for eventual repurposing metformin as an adjuvant drug in oncology; however, evidence-based data are currently needed to establish this. Metformin is a biguanide that in the context of type 2 diabetes primarily targets the liver. Metformin inhibits oxidative phosphorylation which leads to the suppression of gluconeogenesis and causes decrease of blood glucose concentration. Mechanisms responsible for metformin anti-neoplastic effect have been investigated extensively, and key events seem to centralize around its ability to induce intracellular energetic stress with subsequent changes of metabolism resulting in cytostatic or cytotoxic action. Large clinical experience with metformin in the treatment of diabetes together with its plausible effects on different cancer cell types initiated a number of clinical trials that tested the hypothesis that metformin might have a beneficial effect in the treatment of cancer. PURPOSE: The aim of this review is to compile recent advances in our understanding of metformin antineoplastic effects and to give a summary of the results of recent clinical trials of metformin for treatment of different cancer types.
Keywords: cancer; AMPK; clinical trial; metformin; Medical Oncology; Diabetes Mellitus, Type 2; Drug Repositioning; přehodnocení terapeutických indikací léčivého přípravku; diabetes mellitus 2. typu; Antineoplastic Agents; hypoglykemika; Neoplasms; protinádorové látky; zvířata; Humans; nádory; treatment; adjuvantní chemoterapie; Hypoglycemic Agents; diabetes; Chemotherapy, Adjuvant; lékařská onkologie; Metformin; lidé; Animals